Effect of Various Electrolytes on the Phase Separation and Thermodynamic Properties of p‐Tert‐Alkylphenoxy Poly (Oxyethylene) Ether in the Absence/Presence of Drugs. Issue 3 (10th January 2019) - Khan, Muhammad Akhlaqur Rahman; Amin, Md. Ruhul; Mahbub, Shamim; Alam, Md. Masud; Rub, Malik Abdul; Hoque, Md. Anamul; Khan, Mohammed Abdullah; Asiri, Abdullah M.
Abstract: Cloud point (CP) measurements of 4‐(1, 1, 3, 3‐tetramethylbutyl) phenyl‐polyethyleneglycol (Triton X‐100 (TX‐100)) were performed in aqueous solution in the presence of drug Amikacin sulfate (AS)/Neomycin sulfate (NS)/(AS/NS+ different inorganic salts). In aqueous solution, the CP values of TX‐100 first decrease with increasing concentration and then increase with increasing surfactant concentration. The CP values of TX‐100 solutions were found to increase with the increasing concentration of the AS/NS drug. The CP values of TX‐100‐AS/NS mixtures were also observed to decrease with the increase of the concentration of salt. Different thermodynamic parameters such as standard free energy ( Δ G c 0 ), standard enthalpy ( Δ H c 0 ) as well as the standard entropy ( Δ S c 0 ) change of phase separation were calculated and discussed in relation to molecular interactions. Abstract :